Organization of Emergency Care for Children on the Outpatient Stage - Elena M. Kozlova; Ekaterina G. Novopoltseva (Педиатрическая фармакология)
The article considers the principles of emergency care at the outpatient stage, clarifies the terms, and analyzes the regulatory framework. The example of anaphylactic shock and respiratory failure management shows the most crucial details of proper emergency room organization. The importance of continuous simulation training of nursing staff and outpatient doctors is emphasized.